O olhar do intérprete de língua indígena sobre a educação escolar ofertada a estudantes indígenas em escolas de cidades do estado de Goiás - Souza, Valéria Cavalcante da Silva (2024)
This dissertation analyzes the contingencies of the inclusion of indigenous students outside their indigenous lands in an urban context within schools in the State Education Network and the challenges of implementing, since 2015, a proposal from the Goiás State Department of Education (SEDUC-GO) with the hiring of interpreters of indigenous languages to support these students. It presents results of documentary research on the proposal, the correlation with legislation for indigenous school education and research in schools in the State Education Network of the State of Goiás, specifically in the municipalities of Goiânia and Aragarças, which received indigenous students, enrolled among the years from 2015 to 2022, who are outside their indigenous lands due to several factors. It focuses on the views of these indigenous language interpreter teachers regarding their experience as interpreters, with school education and in cities. The approach is both qualitative and quantitative, employing semi-structured interviews, observation and field diaries as methods and techniques. Considering that SEDUC's proposal for interpreters of indigenous languages aims to promote the inclusion and reception of indigenous students who are “in a situation of itinerantity”, from an intercultural perspective, this dissertation reflects on the relationships established between indigenous and non-indigenous people and the actions involving pedagogical practices in the school environment.